Meningothelial hamartoma of scalp mimicking encephalocele in an infant: A case report and review of literature - Amit Kumar Yadav; Workalemahu A. Belachew (Indian Journal of Pathology and Microbiology)
An extremely rare benign lesion of the scalp is reported in a 2-month-old infant. The lesion had been present since birth. On examination, a 3 × 4 cm skin-colored soft mass over the occipital midline area was observed. On ultrasound, a diagnosis of occipital encephalocele was suggested. A complete excision of the mass was performed. Histological examination showed a subcutaneous lesion, which showed haphazardly arranged epithelioid cell nests admixed with connective tissue components, adipose tissues, and pseudovascular patterns within the deep dermis. Immunohistochemistry showed positive expression of Epithelial membrane antigen (EMA) and Vimentin. Tumor cells showed negative expression for Glial Fibrillary acidic protein (GFAP), chromogranin, S-100, Smooth muscle actin (SMA), and CD 34. Based on the clinical presentation, histologic features, and results of ancillary studies, a diagnosis of meningothelial hamartoma of the scalp was given. The clinical behavior of this lesion is benign but it often causes diagnostic confusion and may mimic malignant tumors. It is crucial to recognize the main features of this lesion.